Quikscat Radiometer (QRad) rain rates level 2B data product - Kasparis, Takis; Ahmad, Khalil A.; Jones, Wilma L. (My University, 2006)
The scatterometer SeaWinds onboard the QuikSCAT satellite measures the ocean normalized radar cross section to infer the surface wind vector. In addition, SeaWinds simultaneously measures the polarized microwave brightness temperature of the ocean/atmosphere, and this passive microwave measurement capability is known as the QuikSCAT Radiometer (QRad). Microwave brightness temperatures measured by QRad are used to infer instantaneous rain rates over oceans using a statistical retrieval algorithm that has been developed using collocated QRad brightness temperatures with Tropical Rainfall Measuring Mission (TRMM) Microwave Imager (TMI) rain rate measurements. In this paper, QRad retrieved rain rate examples are presented and comparisons are made with the standard TRMM 2A12 data product. Validation results demonstrate that QRad rain measurements agree well with these independent microwave rain observations. QRad rain estimates starting from 1999 will be available in JPL reprocessing of QuikSCAT winds as part of the level 2B science data product. These rain estimates can be potentially used to improve flagging of rain-contaminated oceanic wind vector retrievals. Moreover, the broad swath coverage of QRad affords additional independent sampling of the oceanic rain, thus, QRad rain retrievals have the potential for contributing to NASA's Precipitation Measurement Mission objectives of improving the global sampling of oceanic rain within 3 hour windows.
Keywords: Geoscience; Signal processing; Microwave circuits; Radiometers